Antidiabetic Activity of Compounds Isolated from the Kernel of Mangifera indica in Alloxan Induced Diabetic Rats - Amran, Md. Shah; Sultan, Md. Zakir; Rahman, Asma; Rashid, Mohammad A (Dhaka University Journal of Pharmaceutical Sciences, 2013)
Diabetes is one of the major causes of death in Bangladesh. A lot of medicinal plants are available in Bangladesh and they possess remarkable antidiabetic activities. The main purpose of this project was to find out the new antidiabetic compound(s) from plants available in our locality. As such an attempt has been made to isolate the antidiabetic compounds from the kernel of mango. Solvent extractions followed by column and thin layer chromatographic techniques were used to purify the compounds. 1H-NMR spectroscopy was used to identify the purified compounds which might have antidiabetic property. Dhaka Univ. J. Pharm. Sci. 12(1): 77-81, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16304